Fluid Viscous Dampers for seismic protection of bridges: a State of the Art - Zoccolini, L.; Bruschi, E.; Pettorruso, C.; Rossi, D.; Quaglini, V. (Procedia Structural Integrity, 2024)
Fluid Viscous Dampers (FVDs) are particular devices that dissipate energy through the lamination of a viscous fluid forced by a piston to pass through an orifice or a valving system. These devices are capable of dissipating large amounts of energy without significantly altering the inherent stiffness of the structure, with a response that strictly depends on the velocity. Therefore, FVDs have been largely employed in bridges since the mid-1990s with the aim of accommodating service slow motions (like thermal motions) and guaranteeing protection from seismic and wind loads that occur at significant speeds. FVDs are suitable both for retrofitting existing vulnerable bridges and for designing new ones. The aim of this paper is to present the evolution of FVDs for the seismic protection of bridges, moving from the first application with passive FVDs to modern devices such as semi-active FVDs, electrorheological, magnetorheological, variable stiffness, and variable damping dampers. Due to the increasingly large number of available devices, this work does not attempt to present a complete state-of-the-art on the subject but focuses on discussing the main milestones as well as the most relevant drawbacks. Devices selected for discussion are shown from a historical perspective and, according to the authors, represent pioneer original steps in the field of seismic protection of bridges with dampers.